Początki misji kameruńskich w kleszczach polityki kolonialnej - Różański, Jarosław (Annales Missiologici Posnanienses, 2023)
Christian missions in Cameroon were quite closely related to European colonization. It came with noble slogans of bringing civilization and freedom. But it had primarily economic and political goals. Although missionary activity was born from other motives, it was nolens volens entangled in the politics of the colonial states. The Cameroonian coast nominally belonged for centuries to Portugal. At the end of the 18th century the missionary activity in Africa had almost completely disappeared. The beginnings of the mission in Cameroon were entangled in the intricate politics of England, Germany, and France in particular. Without this political dimension it is impossible to fully understand the contemporaneity of the various Christian denominations in Cameroon.